Hysterectomy at Aminu Kano Teaching Hospital Kano, Nigeria: A 2 year review - Yusuf M; Abba Z; Takai UI (Ibom Medical Journal, 2018)
BACKGROUND: Hysterectomy is the most frequently performed major gynaecological operation worldwide. Globally, over 1.2million women undergo this surgery annually. This has led to a major controversy that hysterectomies are being performed for unnecessary reasons.